2019
DOI: 10.1371/journal.pone.0217605
|View full text |Cite
|
Sign up to set email alerts
|

PITX1 protein interacts with ZCCHC10 to regulate hTERT mRNA transcription

Abstract: Telomerase is a ribonucleoprotein ribonucleic enzyme that is essential for cellular immortalization via elongation of telomere repeat sequences at the end of chromosomes. Human telomerase reverse transcriptase ( hTERT ), the catalytic subunit of telomerase holoenzyme, is a key regulator of telomerase activity. Telomerase activity, which has been detected in the majority of cancer cells, is accompanied by hTERT expression, suggesting that this… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 53 publications
1
17
0
Order By: Relevance
“…Recent studies have shown that TSGs can cooperate with many nearby genes that are deleted together, which results in a more invasive disease 43 . We have previously reported that PITX1 , a negative regulator of hTERT , interacts with zinc finger CCHC-type containing 10 ( ZCCHC10 ) to regulate hTERT transcription, and both genes are encoded together in the 5q31.1 region 44 . Therefore, chromosome engineering technologies that can transfer an entire chromosome or chromosomal fragments, which contain the essential genomic context for regulation of gene transcription, may enable elucidation of tumor suppressor functions by specific chromosomal domains 45 .…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that TSGs can cooperate with many nearby genes that are deleted together, which results in a more invasive disease 43 . We have previously reported that PITX1 , a negative regulator of hTERT , interacts with zinc finger CCHC-type containing 10 ( ZCCHC10 ) to regulate hTERT transcription, and both genes are encoded together in the 5q31.1 region 44 . Therefore, chromosome engineering technologies that can transfer an entire chromosome or chromosomal fragments, which contain the essential genomic context for regulation of gene transcription, may enable elucidation of tumor suppressor functions by specific chromosomal domains 45 .…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that TSGs can cooperate with many nearby genes that are deleted together, which results in a more invasive disease 41 . We have previously reported that PITX1, a negative regulator of hTERT, interacts with zinc nger CCHC-type containing 10 (ZCCHC10) to regulate hTERT transcription, and both genes are encoded together in the 5q31.1 region 42 . Therefore, chromosome engineering technologies that can transfer an entire chromosome or chromosomal fragments, which contain the essential genomic context for regulation of gene transcription, may enable elucidation of tumor suppressor functions by speci c chromosomal domains 43 .…”
Section: Discussionmentioning
confidence: 99%
“…Cell culture was performed as described previously 37 . A2058 cells were obtained from the Japanese Collection of Research Bioresources Cell Bank (Osaka, Japan).…”
Section: Methodsmentioning
confidence: 99%
“…Analysis of apoptosis was performed as described previously 37 . Apoptotic cells were measured by Annexin V staining using an APC Annexin V apoptosis detection kit with 7-AAD according to the manufacturer's (BioLegend, San Diego, CA, USA) instructions.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation